CO-CREATION AND DELIVERY PERFORMANCE IN OIL AND GAS FIRMS IN PORT HARCOURT - Ademe, D. G; Adewuyi, O. S (Scholar Express Journals, 2021)
The study examines the association between co-creation and delivery performance of oil and gas firms in Port Harcourt. The aim of this study is to examine the relationship between co-creation and delivery performance of oil and gas firms in Port Harcourt. The study adopted quasi-experimental research design method. Two hundred and thirty-seven (237) copies of questionnaires were distributed, two hundred and two (202) copies were fit for analysis. Multiple regression Statistical tool was adopted with the aid of Statistical Package for Social Sciences (SPSS version 21). The findings of the study showed that co-creation significantly relates with delivery performance. Based on the findings, the study recommended that managers of oil and gas firms should collaborate with customer to co-create for the betterment of the organization
Keywords: Customer Participation Behaviour; Customer Citizenship Behaviour; Delivery Reliability; Delivery Speed